Adolescent social rejection alters pain processing in a CB1 receptor dependent manner - Schneider, Peggy; Spanagel, Rainer; Schneider, Miriam (European neuropsychopharmacology, 2016)
Experiences of social rejection represent a major source of distress and in particular peer rejection during adolescence has been implicated in various psychiatric disorders. Moreover, experimentally induced acute social rejection alters pain perception in humans, implicating overlapping neurocircuits for social and physical pains. We recently demonstrated that rearing of adolescent Wistar rats with inadequate, less playful play partners (Fischer 344) persistently decreases pain sensitivity, although the detailed mechanisms mediating the aversiveness during the social encounter remained unsettled. With the present study we examined the behavioral performance during acute interaction of female adolescent Wistar rats with either age-matched same-strain partners or rats from the Fischer 344 strain. We here identify the low responsiveness upon playful attacks, which appears to be characteristic for social play in the Fischer 344 strain, as one of the main aversive components for adolescent Wistar animals during cross-strain encounters, which subsequently diminishes thermal pain reactivity. A detailed behavioral analysis further revealed increased ultrasonic vocalization at 50kHz and an increased frequency of playful attacks for adolescent Wistar animals paired with a Fischer 344 rat compared to same-strain control pairs. Finally, an acute injection of a subthreshold dose of the cannabinoid type 1 receptor inverse agonist/antagonist SR141716 before the social encounter abolished enhanced play-soliciting behavior in Wistar/Fischer 344 pairs as well as the behavioral consequences of the rejection experience in adolescent Wistar rats, further emphasizing an important modulatory role of the endocannabinoid system in mediating the effects of social behavior and social pain.
Gesehen am 10.07.2019